Respostas

2014-06-26T20:33:41-03:00
x         y 
0         3 ⇒ 3 = a * 0 + b  ⇒ {0 + b = 3
5         0 ⇒ 0 = a * 5 + b ⇒  {5a + b = 0

Método da adição:
0 + b = 3  ⇒ Multiplica-s os dois termos por (- 1)
5a + b = 0

0 - b = - 3
5 + b = 0          
5a = - 3
a = - 3 : 5
a = - 0,6

Valor de b:
5a + b = 0
5 * (- 0,6) + b = 0
- 3 + b = 0
b = 0 + 3
b = 3

f (x) = ax + b
f (x) = - 0,6x + 3
2014-06-26T20:38:10-03:00
M = 0 - 3 = -3
      5 - 0      5

y - 0 = -3/5(x - 5)
y = -3/5x + 3 -> equação reduzida

-3/5x - y + 3 = 0 -> equação geral